THE ROLE OF GENERATIVE AI IN THE AUTOMATION OF LEGAL DOCUMENT PREPARATION: AN ANALYSIS OF ACCURACY, EFFICIENCY, AND ETHICAL ASPECTS - Shamov, O. A. (Systems and Technologies, 2025)
This article explores the transformative impact of generative artificial intelligence (AI) on legal practice, with a particular focus on the preparation and analysis of legal documents. It examines modern generative AI models, their capabilities, limitations, and the risks associated with their implementation in the legal domain. The aim of the article is to analyze the current state of generative AI applications for automating legal tasks, identify key issues related to the accuracy and reliability of generated content, and propose a hypothetical model to enhance the trustworthiness of AI-generated outcomes. To achieve this, the article sets out the following objectives: to review recent academic research and publications evaluating the effectiveness and precision of large language models (LLMs) in legal tasks; to identify the unresolved issue of factual verification of generated content; and to formulate and justify a hypothesis for improving baseline research results through the implementation of a hybrid architecture. The study employs methods of systems analysis, comparative analysis of empirical studies, synthesis, and modeling. It analyzes foundational research on structured approaches to AI-assisted legal document analysis and the outcomes of comparative tests between LLMs and human legal professionals, highlighting the persistent challenge of factual accuracy in AI-generated content The article proposes a hypothesis that integrating structured prompting techniques with a Retrieval-Augmented Generation (RAG) architecture-leveraging a curated and dynamically updated legal knowledge basecan significantly improve the factual precision and reliability of AI-generated legal documents. This hypothesis is substantiated with a formalized expression and a potential mechanism for implementation and verification. The proposed approach is shown to not only minimize the risk of AI "hallucinations" but also to lay the groundwork for the development of more responsible and ethical tools that augment, rather than replace, the professional competencies of legal practitioners.